The impact of information technology and organizational structure on job satisfaction among academic staff at Al-Azhar University in Palestine - Albaz, Mohamed F.M (2014)
Many organizations have experienced some kind of changes in the way they do things. Structural changes, for example, have bearings on how employees feel about their work. So do changes in technology and organizational structure. Because these factors in the work environment have implications to employees attitudes toward work, the main aim of the present study was to investigate such implication. In particular, the present study attempted to examine the influence of these factors on job satisfaction through testing two hypotheses developed. Toward this end, a survey was carried out that involved distribution of questionnaires to 180 employees of Al-Azhar University Gaza in Palestine, who comprise both academic and non academic staff and who were randomly selected as participants. The findings reveal that use of IT and organizational structure significantly influence job satisfaction, and thus supporting the hypotheses formulated. It is further revealed that amongst the three independent variables, use of IT and organizational structure appear to be the most important predictor of job satisfaction.The findings have important implications to practice and future research, which are highlighted here. In addition, the study's limitations are also discussed.